Implementasi Pembelajaran Bahasa Arab Pada Tingkatan MI - Sapri Sapri; Siti Halisya Parapat; Sayang Pasaribu; Azwar Siregar; Rili Ritami Sipahutar; Putri Novia Ramayani Siregar; Anisa Pratiwi; Wanda Amelia Purba (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This article discusses the implementation of learning at MI which links mixed learning, namely online and offline. In this case, there is Bleanded Learning, namely mixed learning. This research was conducted using a literature review method and literature study by examining several articles that discussed issues related to the problem. The aim of this research is that this article is able to provide an overview of the implementation of Arabic language learning in the modern era, which makes it easier for students and educators. The results of this research are that technology can be a tool for implementing learning through applications that focus on Arabic language learning.